Integrating Turath and Modern Knowledge in Islamic Higher Education - Sami Barkah; Mohieddin Masoud; Salem Aladi; Nahid Ayad; Safa Alrumayh; Hajer Albshkar; Mowafg Masuwd (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2026)
Islamic higher education encounters a continuous challenge in integrating classical Islamic heritage (Turath) with modern knowledge in a consistent and meaningful way. This study examines to which extent Islamic education programs balance Turath (classical Islamic heritage) and modern knowledge in the Faculties of Sharia and Islamic Studies at the University of Zawia, Libya. Using a mixed-methods explanatory sequential design, quantitative data were collected from 350 students through a structured questionnaire, followed by qualitative interviews with 20 lecturers to provide deep insights. The findings indicate that students demonstrate a high appreciation for both Turath (M = 4.34, SD = 0.79) and modern knowledge (M = 4.08, SD = 0.96), reflecting strong support for an integrative model of Islamic education. However, curriculum balance was rated at a moderate level (M = 3.35, SD = 1.07), suggesting that integration between the two domains remains insufficient. Teaching practices were also perceived as moderately effective (M = 3.73, SD = 0.96), with limitations in fostering critical engagement and application. Furthermore, students identified significant challenges (M = 4.09, SD = 0.90), particularly the overreliance on memorization, weak linkage between theory and practice, and limited institutional coordination. Qualitative findings confirm that these challenges rooted in structural fragmentation, lack of a unified curriculum framework, and insufficient pedagogical training. The study concludes that while the conceptual foundation for integration exists, effective implementation requires systematic curriculum reform, pedagogical innovation, and institutional integration.